Relationship Between Standardized Measures of Chronic Kidney Disease-associated Pruritus Intensity and Health-related Quality of Life Measured with the EQ-5D Questionnaire: A Mapping Study - Monica Hernandez Alava; Alessandro Sasso; Pann Ei Hnynn Si; Matthew Gittus; Richard Powell; Louese Dunn; Praveen Thokala; James Fotheringham (Medical Journals Sweden, 2023)
Chronic kidney disease-associated pruritus is linked with decreased health-related quality of life assessed using disease-specific instruments. The extent to which worsening pruritus reduces generic quality of life assessed using the EQ-5D instrument is unknown. Prevalent kidney failure patients receiving in-centre haemodialysis from 5 centres completed the EQ-5D-5L quality of life measure, worst Itching Intensity Numerical Rating Scale and 5-D itch pruritus instruments. Latent class models were used to identify clusters of patients with similarly affected body parts, and mixture models were used to map the pruritus measures to the EQ-5D. Data on 487 respondents were obtained. Latent class analysis identified 3 groups of patients who had progressively worsening severity and an increasing number of body parts affected. Although the worst itching intensity numerical rating scale and 5-D itch instruments correlated with each other, only the latter had a strong relationship with EQ-5D. When controlling for age, sex, diabetes and years receiving dialysis, the meanpredicted EQ-5D utility (1: perfect health, 0: dead) decreased progressively from 0.69 to 0.41. These findings suggest that pruritus instruments that include domains capturing how the individual is physically, mentally and socially affected by their pruritus, in addition to severity, more closely approximate the EQ-5D generic quality of life measure.